Development of tissue bank - R. P. Narayan (Indian Journal of Plastic Surgery)
The history of tissue banking is as old as the use of skin grafting for resurfacing of burn wounds. Beneficial effects of tissue grafts led to wide spread use of auto and allograft for management of varied clinical conditions like skin wounds, bone defects following trauma or tumor ablation. Availability of adequate amount of tissues at the time of requirement was the biggest challenge that forced clinicians to find out techniques to preserve the living tissue for prolonged period of time for later use and thus the foundation of tissue banking was started in early twentieth century. Harvesting, processing, storage and transportation of human tissues for clinical use is the major activity of tissue banks. Low temperature storage of processed tissue is the best preservation technique at present. Tissue banking organization is a very complex system and needs high technical expertise and skilled personnel for proper functioning in a dedicated facility. A small lapse/deviation from the established protocol leads to loss of precious tissues and or harm to recipients as well as the risk of transmission of deadly diseases and tumors. Strict tissue transplant acts and stringent regulations help to streamline the whole process of tissue banking safe for recipients and to community as whole.